All Days 2008
DOI: 10.2118/113746-ms
|View full text |Cite
|
Sign up to set email alerts
|

Fiber Sweeps for Hole Cleaning

Abstract: Cuttings transport in highly deviated wellbores is more challenging and critical than in vertical wells. In inclined wells, the fluid velocity has a reduced vertical component that may not be sufficient to transport all the cuttings to the surface. When cuttings returns do not appear to be sufficient for the drilling rate, hole cleaning sweeps are applied to clean the borehole or reduce cuttings bed thickness. Fiber-containing sweeps have been very effective in cleaning highly deviated and extended reach wells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…The effectiveness of using fiber sweep for hole cleaning and reduction of cutting bed thickness in horizontal and highly deviated sections was recently considered [1,2,10]. Valluri et al [10] investigated the effect of rheology of the sweep fluid on sweep efficiency under LPAT and EPET conditions.…”
Section: Fig 1: Schematic Diagram Of a Close Flow Loopmentioning
confidence: 99%
See 2 more Smart Citations
“…The effectiveness of using fiber sweep for hole cleaning and reduction of cutting bed thickness in horizontal and highly deviated sections was recently considered [1,2,10]. Valluri et al [10] investigated the effect of rheology of the sweep fluid on sweep efficiency under LPAT and EPET conditions.…”
Section: Fig 1: Schematic Diagram Of a Close Flow Loopmentioning
confidence: 99%
“…It was reported that, in the absence of drill pipe rotation, high viscosity and high density sweeps were found to be ineffective in a horizontal configuration and temperature affects the sweep efficiency by changing the rheological properties of drilling fluid. Ahmed and Takach [1] conducted hole cleaning performance of a fiber sweep and discovered that the Xanthum gum mixed with synthetic fiber has better hole cleaning capacity than when mixed with base fluid in horizontal well configuration. Similarly, Cheung et al [2] conducted experiments with drillpipe rotation speeds (0 -90 rpm) and different fiber concentrations.…”
Section: Fig 1: Schematic Diagram Of a Close Flow Loopmentioning
confidence: 99%
See 1 more Smart Citation
“…Equilibrium bed heights were measured at different sweep flow rates in horizontal and inclined configurations. [12] described and modeled a simple and more reliable artificial neural network (ANN) for various borehole conditions using some critical parameters associated with foam velocity, foam quality, hole geometry, subsurface condition (pressure and temperature) and pipe rotation. The average absolute percent relative error (AAPE) between the experimental cuttings concentration and ANN model is less than 6%, and using MLR, AAPE is less than 9%.…”
Section: Introductionmentioning
confidence: 99%